2013
DOI: 10.1088/1748-9326/8/4/044036
|View full text |Cite
|
Sign up to set email alerts
|

Historical trends in greenhouse gas emissions of the Alberta oil sands (1970–2010)

Abstract: There has been increased scrutiny of the Alberta oil sands due to their high carbon intensity (CI) relative to conventional crude oil. Relying entirely on public and peer-reviewed data sources, we examine historical trends in the CI of oil sands extraction, upgrading, and refining. Monthly data were collected and interpolated from 1970 to 2010 (inclusive) for each oil sands project. Results show a reduction in oil sands CI over time, with industry-average full-fuel cycle (well-to-wheels, WTW) CI declining from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 11 publications
1
33
1
Order By: Relevance
“…Fig. 4 shows a comparison of electricity estimated by this research to electricity consumption reported by major SAGD operators against the SOR of the projects [49,50]. As can be observed, the electricity intensity estimated by this research is representative of electricity intensity reported by majority of SAGD operators.…”
Section: Sagdmentioning
confidence: 72%
See 4 more Smart Citations
“…Fig. 4 shows a comparison of electricity estimated by this research to electricity consumption reported by major SAGD operators against the SOR of the projects [49,50]. As can be observed, the electricity intensity estimated by this research is representative of electricity intensity reported by majority of SAGD operators.…”
Section: Sagdmentioning
confidence: 72%
“…The natural gas consumed in the process also depends on the amount of coproduced gas. Produced gas in SAGD ranges from 1 to 89 m 3 /m 3 of bitumen [44,49,50]. Most of the produced gas is conserved and utilized so as to reduce the natural gas demand of the plant while a portion of it is flared.…”
Section: Steam Assisted Gravity Drainage (Sagd)mentioning
confidence: 99%
See 3 more Smart Citations